Health Beliefs, Behavior, Spiritual Growth, and Salvation in a Global Population of Seventh-day Adventists - McBride, Duane C. (Review of religious research, 2021)
Background: The Seventh-day Adventist Church is a growing global denomination with strict substance use abstinence and recommended dietary requirements that together are called the "Health Message." Abstinence from alcohol and tobacco is a requirement of membership and a plant-based diet is strongly advised.PurposeWhile a wide variety of research has reported the Adventist health advantage, very little research has been conducted on Adventist members’ attitudes toward and adherence to the Health Message. This research examines members views, from a global survey, about the health message, personal adherence, and belief that adherence ensures salvation.MethodsThe survey was conducted in 2017/2018 with a total N of 63,756. The questionnaire was translated into about 60 languages and then back translated into English for improved accuracy.ResultsOver 80% of the respondents reported that they agreed the Adventist health message was wholisitic, core to Adventist beliefs, supported by science, and increased the probability of a longer life. There were very few differences by global regions. About 80% also agreed that they should abstain from tobacco and alcohol and follow a healthy diet. However, about 45% believed that they could pick and choose which parts to follow with only a little over one-third reporting that they followed the Health Message a great deal. Strict adherence appeared to be in abstinence from alcohol (91%) and tobacco (97%). Only about 19% reported being vegetarian or vegan. Over 47%, mostly in the Southern Hemisphere, reported the belief that if they kept the Health Message completely, they would be assured of salvation, though this is at odds with formal doctrine.Conclusions and ImplicationsThe data suggest that church leadership has been successful in obtaining global acceptance of the Health Message, convincing members of its scientific basis, and to abstain from tobacco and alcohol use. However, the data also show almost half of members believe that they can pick and choose elements to follow. In addition, these data have major implications for church leadership in disentangling the implications and expectations of the Health Message from the Church’s fundamental belief that salvation is only through faith in Christ.